Molluscan biological and chemical diversity: secondary metabolites and medicinal resources produced by marine molluscs - Benkendorff, Kirsten (Biological reviews of the Cambridge Philosophical Society, 2010)
The phylum Mollusca represents an enormous diversity of species with eight distinct classes. This review provides a taxonomic breakdown of the published research on marine molluscan natural products and the medicinal products currently derived from molluscs, in order to identify priority targets and strategies for future research. Some marine gastropods and bivalves have been of great interest to natural products chemists, yielding a diversity of chemical classes and several drug leads currently in clinical trials. Molluscs also feature prominently in a broad range of traditional natural medicines, although the active ingredients in the taxa involved are typically unknown. Overall secondary metabolites have only been investigated from a tiny proportion (<1%) of molluscan species. At the class level, the number of species subject to chemical studies mirrors species richness and our relative knowledge of the biology of different taxa. The majority of molluscan natural products research is focused within one of the major groups of gastropods, the opisthobranchs (a subgroup of Heterobranchia), which are primarily comprised of soft‐bodied marine molluscs. Conversely, most molluscan medicines are derived from shelled gastropods and bivalves. The complete disregard for several minor classes of molluscs is unjustified based on their evolutionary history and unique life styles, which may have led to novel pathways for secondary metabolism. The Polyplacophora, in particular, have been identified as worthy of future investigation given their use in traditional South African medicines and their abundance in littoral ecosystems. As bioactive compounds are not always constitutively expressed in molluscs, future research should be targeted towards biosynthetic organs and inducible defence reactions for specific medicinal applications. Given the lack of an acquired immune system, the use of bioactive secondary metabolites is likely to be ubiquitous throughout the Mollusca and broadening the search field may uncover interesting novel chemistry.